Analisis Suku Bunga Kredit terhadap Keputusan Pengambilan Kredit pada Perusahaan Pembiayaan di Kota Batam - Vargo Christian L. Tobing; Hendri Herman (LPPM Universitas Putera Batam, 2020)
Credit is a facility provided by the owner of the fund to the party that needs the funds with the provision stipulated in the credit agreement, including interest rates. Interest rates are used as a benefit to the lender because it has lent funds to debtors. This research aims to look at the effect of credit rates on credit-making decisions on financing companies in Batam. The object of this research is the financing company that exists in the city of Batam. The respondents in this study were customers who borrowed from financing companies. The determined customer who applied for credit as a respondent is due to the purpose of this study to see the decision of credit making. The number of respondents in this study was 96 respondents. Data is obtained by disseminating questionnaires to respondents. Data that has been obtained, tabulated and analyzed using the SPSS program. The data analysis used in this study is data quality test, normality test, heteroskedastisity test, determination coefficient analysis, partial hypothesis test. From the results of the study, it was obtained that the interest rate of credit was significant to the decision-making of the credit, the correlation value in this study was 65.5% which means that the loan interest rate is able to explain the decision of the credit making at 65.5%, while the remaining 34.5% is explained by other variables that were not included in this study.